Quality assessment of controlled clinical trials published in Orthopaedics and Traumatology journals in Spanish: An observational study through handsearching and evidence mapping (2018)
Few Orthopaedics and Traumatology journals from Latin America and Spain are indexed in major databases; controlled clinical trials published in these journals cannot be exhaustively retrieved using electronic literature searches. We aimed to identify, describe and assess the quality of controlled clinical trials published in Orthopaedics and Traumatology journals from Latin America and Spain through handsearching and evidence mapping methods. We identified controlled clinical trials published in eligible Orthopaedics/Traumatology journals in Spanish until July 2017 by handsearching. Data were extracted for controlled clinical trials main characteristics and the Cochrane risk of bias tool was used to assess the controlled clinical trials methodological quality. In addition, we mapped the main findings of these trials. As a result, we assessed 5631 references in 29 eligible journals of which 57 were controlled clinical trials (1.0%). Controlled clinical trials were published between 1995 and 2017 at a rate of 2.5 per year. Journals from Spain and Mexico published around 63% of the controlled clinical trials identified. The median sample size of patients enrolled was 60 (range=30–300 participants). About conditions assessed, 38.5% of controlled clinical trials assessed issues related to knee conditions, 15.7% about hip and 10.5% about trauma or spine. The risk of bias domains most affected was selective reporting bias and random sequence generation. In addition, only two and seven trials had low risk of bias in all items related to participant/personnel and outcome assessment blindings, respectively. More than 40% of studies did not report differences on benefits/harms between the interventions assessed. As a conclusion, the number of controlled clinical trials published in Orthopaedics/Traumatology journals from Latin America and Spain is low. These controlled clinical trials had important methodological shortcomings and were judged as unclear or high risk of bias. These trials are now available in CENTRAL for their potential inclusion in systematic reviews and other documents of synthesis.